Proses Produksi Program KOLAK di TVMU Dalam Menerapkan Nilai Dakwah Kemuhammadiyahan - Hiru Muhammad; Zahwa Indira; Istisari Bulan Lageni (Journal on Education, 2023)
TVMu, officially aired on November, 18, 2013, coincided with the 101st anniversary of Muhammadiyah. To fulfill the four functions of Communications, namely educations, information, social control and entertainment, TVMu created program called KOLAK, Actual Opinion Religion and Culture. This program presented by the Secretary General of Muhammadiyah Central Executive, Prof. Dr. Abdul Mu’ti, M.Ed. This program elaborates on Muhammadiyah preaching related to contemporary issues and challenges. Throughout its production until completion, the KOLAK program always strives to ensure that Muhammadyah’s preaching is connected to relevant issue. This research employs a qualitative method and utilizes the theory of Segmentation, Targeting, Positioning, while for the production process, the program utilizes Herbert Zettl’s theory, wich cover everything from pre-production to post-production. The research finding show that the KOLAK program undergoes all stages of broadcast program planning the ensure its acceptance by its target audience, namely the Muhammadiyah Community.